Avaliação nutricional da semente de canola extrusada ou não, para leitões em fase de creche - Scherer, Carina (2006)
Two experiments were carried out to evaluate extruded and non-extruded canola seed for nursery piglets. For the digestibility trial, fifteen crossbred barrows with initial average body weight of 19.79±1,43kg were allocated in metabolism cages, in a completely randomized design with three treatments and five replications, being one animal per experimental unit. There were evaluated non-extruded canola seed (NECS) and extruded canola seed (ECS), which had replaced 20% of the basal diet. The digestibility coefficients of dry matter (DM), crude protein (CP), ether extract (EE), organic matter (OM) and gross energy (GE) were, respectively, 65.43; 69.65; 74.71; 65.98 and 62.82% for NECS and 79.39; 69.57; 92.85; 80.47 and 81.67% for ECS. The values of DM digestibility, digestible protein, EE digestibility, OM digestibility and digestible energy, on dry matter basis, were, respectively, 62.32; 14.98; 30.50; 63.83% and 4.197 kcal/kg for NECS, and 76.34; 21.34; 35.27; 78.20% and 5.234 kcal/kg for ECS. For the performance trial, fifty-six crossbred piglets were used, 50% male and 50% female, with initial average body weight of 15,03±1,8kg. Piglets were divided into seven treatments in a completely randomized design, with four replications and two animals per experimental unit. Treatments were consisted of a control diet and six diets with 6, 12 and 18% of NECS or ECS inclusion. No differences (P>0,05) were found for animal performance, however there was a linear decrease (P<0,05) in feed intake and diet cost per kilogram of weight gain for diets with NECS and ECS, while increasing the inclusion level. Canola seed, extruded or not, can be included in diets of nursery piglets up to 18% without performance damage. Including 18% of ECS promoted smaller cost per kilogram of animal